Effects of acupuncture on Luteinized Unruptured Follicle Syndrome: A meta-analysis of randomized controlled trials. (March 2020) - Liu, Xiaojuan; Shi, Wenying; Liu, Zhifeng; Shi, Shuqing; Ke, Chao; Zhang, Peiming; Tan, Zhenyu; Zhang, Wei
Highlights: Few researches have summarize the effects of acupuncture on LUFS from randomized control trials. We included 10 randomized control trials involving 715 participants in this meta-analysis showing acupuncture alone and acupuncture as an adjunct both could significantly improve ovulation, which was confirmed by Trial Sequential Analysis. Trial Sequential Analysis indicated further more studies needed to testify the effects of acupuncture on pregnancy rate of LUFS. Improved serum luteinizing hormone and estradiol levels, and decreased pulsatility index and resistance index of ovary artery were shown in both two subgroups. Evidences of most outcomes were "low" or "very low", so the results should be cautiously interpreted. Abstract: Purpose: This meta-analysis aimed to evaluate the comprehensive efficiency and safety of acupuncture on Luteinized Unruptured Follicle Syndrome based on Randomized Controlled Trials (RCTs). Methods: Six electronic databases (i.e. Wanfang, VIP, China National Knowledge Infrastructure, Pubmed, Cochrane, and Embase) were searched from inception to July 2019. Randomized controlled trials were eligible to evaluate the effects of acupuncture alone or acupuncture as an adjunct. The primary outcomes were the ovulation rate and pregnancy rate. Two reviewers proceeded study selection and quality assessment of included trials and performed heterogeneity of included studies before meta-analysis.Trial Sequential Analysis was used to assess the risk of random error and estimate required information size. The Grading of Recommendations Assessment, Development and Evaluation was applied for assessing level of evidence. Results: 10 studies involving 715 participants were included Meta-analysis showed acupuncture alone and acupuncture as an adjunct both could significantly improve ovulation, which were confirmed by Trial Sequential Analysis. The evidence of acupuncture improving pregnancy rate was insufficient. Improved serum luteinizing hormone and estradiol levels, and decreased pulsatility index and resistance index of ovary artery were shown in both two subgroups. Level of evidence of most outcomes was "low" or "very low", so the results should be cautiously interpreted. Conclusions: Acupuncture alone or be combined with drugs are effective on Luteinized Unruptured Follicle Syndrome especially for improving ovulation . While concurrent evidence is insufficient, and further studies of high quality are needed to strengthen the conclusion.